Political Event Effect on Politically Connected Firms Return and Trading Volume Activity (Event Study on KOMPAS100) - Sitorus, Ganda Glen Michael; Nainggolan, Yunieta Anny (Journal of Business and Management, 2020)
Abstract. This paper aims to find out the existence of differences between politically connected firms and non-politically connected firms during Indonesia political year. There were numerous events in 2019 that believed to create an uncertainty in the market. In 2019, for the first time in Indonesia history that presidential and legislative elections were held simultaneously and in one day, beside that during that year there were large-scale demonstrations that have occurred more than once in context of rejecting government statements or even new policy. The event study methodology is used to analyse the market reaction toward 3 chosen political events within a 5 days event period. The market reactions are determined by using two indicators of abnormal return and trading volume activity. The samples that will be used is Kompas-100 stock which will be divided into politically connected firms and non-politically connected firms. This overall result of this paper shows that there is no difference between politically connected firms and non-politically connected firms during the specified event. The test actually does show a higher result of AAR for Politically connected firms but the differences were too slight.Keywords: Event Study, Indonesian Political Connection, Political Event, Political Uncertainty